MA SEBAGAI HURUF DAN PERUBAHAN MAKNANYA DALAM BAHASA ARAB - Sufrin Efendi Lubis (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2018)
This type of research is a literature review that seeks meaning and how to know "ma" if it is positioned as a letter. In this research only include "ma" as a letter, meaning and how to know it. Through this research, it is expected to be able to distinguish "ma" as just letters, as well as how to know and examples.As for the results of the study and analysis, the researcher concluded that ma as a letter has 3 (three) main meanings, namely: "Ma" as a letter which means "mashdariyah". This meaning is divided into 2 (two), "mashdariyah" and "mashdariyah zamaniyah". 2. "Ma" as a letter which means "nafiyah", this is also divided into 2 (two), "nafiyah" functions like "laisa" and "nafiyah" which do not function like "laisa". 3. "Ma" as a letter meaning "zaidah", and this is also divided into several parts. But the author only mentions two parts, namely "zaidah kaffah" and "zaidah ghair kaffah"